2015
DOI: 10.1039/c5ra04874e
|View full text |Cite
|
Sign up to set email alerts
|

Reverse iodine transfer polymerization (RITP) of chloroprene

Abstract: It is clear that the polymerization of CP was well-controlled at a low temperature (50 °C) in benzene in the presence of ABVN as initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The difficulty in adapting controlled radical polymerization to CP mainly arises from the fact that the monomer is highly polar and shows a high degree of homopolymerizability, which originate from the electron-rich vinyl group and the electronegative chlorine atom. 18 The controlled radical copolymerization of CP with dimethyl 1,3-butadiene-1-phosphonate was also attained using nitroxide-mediated radical polymerization in xylene. 16 Hui et al demonstrated that RAFT polymerization of CP in benzene using the dithiobenzoate-type RAFT agents afforded poly(CP)s with predetermined molecular weights and low molar mass dispersities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in adapting controlled radical polymerization to CP mainly arises from the fact that the monomer is highly polar and shows a high degree of homopolymerizability, which originate from the electron-rich vinyl group and the electronegative chlorine atom. 18 The controlled radical copolymerization of CP with dimethyl 1,3-butadiene-1-phosphonate was also attained using nitroxide-mediated radical polymerization in xylene. 16 Hui et al demonstrated that RAFT polymerization of CP in benzene using the dithiobenzoate-type RAFT agents afforded poly(CP)s with predetermined molecular weights and low molar mass dispersities.…”
Section: Introductionmentioning
confidence: 99%
“…17 They also reported the synthesis of block copolymers composed a polystyrene or poly(methyl methacrylate) segment by the RAFT polymerization 17 and reversible iodine transfer polymerization of CP in benzene. 18 The controlled radical copolymerization of CP with dimethyl 1,3-butadiene-1-phosphonate was also attained using nitroxide-mediated radical polymerization in xylene. 19 Another example involves the iodine-mediated radical emulsion polymerization of CP.…”
Section: Introductionmentioning
confidence: 99%
“…). It is not surprising, therefore, that the advent of RDRP has seen a number of groups apply various techniques, namely nitroxide‐mediated polymerization (IUPAC term is aminoxyl‐mediated polymerization), atom transfer radical polymerization (ATRP), iodine transfer polymerization, tellurium‐mediated radical polymerization and RAFT ( vide infra ), in attempts to control radical polymerization of conjugated diene monomers and provide a route to low‐dispersity polymers with better defined architecture and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl halides are useful compounds often used in RDRP techniques (such as ATRP, iodine transfer polymerisation (ITP) [47][48][49][50][51][52] , reverse iodine transfer polymerisation (RITP) [53][54][55][56][57][58] and bromine-iodine transformation reversible-deactivation radical polymerisation (BIT-RDRP) [59][60][61][62] ) due to the reversible homolytic scission of the carbon-halogen bond. ATRP uses alkyl halides as initiators whereas ITP employs typically unstable alkyl iodides as a chain transfer agents (CTAs).…”
mentioning
confidence: 99%
“…The alkyl iodides required in ITP processes are difficult to store due to their low bond dissociation enthalpies, which is why focus has shifted to explore the in situ generation of alky iodide compounds from the more stable alkyl bromides in both RITP and BIT-RDRP processes. Despite limited reports in water 63,64 , RITP and BIT-RDRP reactions commonly employ organic solvents, high temperatures (50-110 °C 53,[55][56][57]60 ) and metal-containing reagents (e.g. sodium iodide in BIT-RDRP).…”
mentioning
confidence: 99%